Pengaruh Kerjasama Tim, Knowledge Sharing dan Efikasi Diri terhadap Kinerja Karyawan PT Kluege International - Christin Victoria Sanger; Ferryal Abadi (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to find out how much teamwork, knowledge sharing, and self-efficacy on employee performance. This study uses a quantitative approach with a survey method through distributing questionnaires to 40 employees. The sample for this study was employees of PT Kluege International. Analysis of the data used is the classic assumption test which consists of normality test, multicollinearity test, and heterokesdatisitas test, path analysis, t test and f test. Hypothesis test results (t test) which indicate that the team collaboration variable does not affect the performance of thitung1.101 <ttable 2.030. Knowledge Sharing does not affect performance by tcount 1.866 <ttabel 2.030. Self-efficacy has a significant effect on performance with t count 3.555> t table 2.030, with a coefficient of determination 72.7%